2018
DOI: 10.3390/en11113203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Metal Bipolar Plate Coating on the Performance of Proton Exchange Membrane Fuel Cells

Abstract: Environmental concerns of greenhouse gases (GHG) effect from fossil commodities and the fast increase in global energy demand have created awareness on the need to replace fossil fuels with other sources of clean energy. PEM fuel cell (PEMFC) is a promising source of energy to replace fossil fuels. The commercialization of the cell depends on its price, weight and mechanical strength. Bipolar plates are among the main components of PEMFC which perform some significant functions in the fuel cell stack. Metal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 110 publications
0
37
0
Order By: Relevance
“…Furthermore, Equation (2) was solved considering the convective flux Equation (10). Meanwhile, Equation (10) was solved using the velocity in the pore [17] and mass flux vectors [18,19], and these latter equations were determined by electrode-reaction kinetics [20].…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Equation (2) was solved considering the convective flux Equation (10). Meanwhile, Equation (10) was solved using the velocity in the pore [17] and mass flux vectors [18,19], and these latter equations were determined by electrode-reaction kinetics [20].…”
Section: Methodsologymentioning
confidence: 99%
“…The equations are written in indicial-tensor notation with: ρ, density kg/m 3 ; t, time s; µ dynamic viscosity of oxygen = 2 × 10 −5 Pa-s (5); u, velocity vector m/s; p, pressure Pa; ω i weight fraction of the i th species; with an inlet mass fraction O 2 = 0.1447, a mass fraction of H 2 O = 0.3789, and a mass fraction of N 2 = 0.4764; D e f f ,ij , the effective binary diffusion coefficient (see Equation (4) in [22][23][24]); M, the total molar mass of the mixture g/mol (see Equation (5) in [19][20][21][25][26][27]); M j , the molecular weight of species j, g/mol; MO 2 , the molecular weight of O 2 = 32 g/mol; M H2O , the molecular weight of H 2 O = 18 g/mol; M N2 , the molecular weight of N 2 = 28 g/mol; D ij , the binary diffusion coefficient for species i and j; k, the Maxwell diffusion constant = 3.16 × 10 −8 Pa·m 2 /s; T, temperature = 353 • K; ν i , the molar diffusion volume of the j th species, cm 3 /mol; ν O2 , the molar diffusion volume of O 2 = 16.6 × 10 −6 cm 3 /mol; νH 2 O, molar diffusion volume of H 2 O = 12.7 × 10 −6 cm 3 /mol; νN 2 , the molar diffusion volume of N 2 = 17.9 × 10 −6 cm 3 /mol; for M j , MO 2 , MH 2 O, and MN 2 , see Table 1; ε, porosity = 0.5; i c , cathode current; S a specific surface area = 1 × 10 7 m 2 /m 3 ; δ, active layer thickness = 10 um; i 0 , exchange current density = 1.06 × 10 −6 mA/cm 2 ; F, Faraday's constant = 96485 C/mol, R, gas constant = 8.314 J/(mol·K); η overpotential between 0.2 and 0.82 V; t H 2 O electro-osmotic drag = 3; gdl, gas diffusion layer thickness = 0.2 mm.…”
Section: Name Equations Numbermentioning
confidence: 99%
“…All the achievements recorded so far in the fuel cell technology has been due to continued research on PEM fuel cell and renewable energy in general [149][150][151][152][153][154][155][156][157][158][159][160]. Discussions in this work showed that a comprehensive knowledge of materials and properties is necessary toward choosing the correct preparation method.…”
Section: Future Workmentioning
confidence: 95%
“…The major challenges are related to the high initial capital cost needed in the execution of most renewable energy projects and the underdeveloped technologies for harnessing the energy for some renewable sources.. Such challenges hamper the advancement of most renewable sources into full commercialization [5][6][7]. Today different types of renewable sources are springing up like the enhanced geo thermal, concentrated solar photovoltaics, ocean energy etc.…”
Section: Introductionmentioning
confidence: 99%